2016
DOI: 10.17795/jhealthscope-40240
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead Ions from Aqueous Solution by Nano Zero-Valent Iron (nZVI)

Abstract: Background: The nanoscale zero-valent iron (nZVI) has good potential for heavy metals removal from aqueous solution because it has special physicochemical properties. In addition, it could remove Lead from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Considering the soil complexity, it is essential to set the concentration of the treatment reagents matching the contaminants. It is reported that the nZVI performed a higher removal efficiency when the molar ratio of nZVI/lead and nZVI/nitrate is 10 and 4 respectively in the solution (Su et al 2014, Moazeni et al 2017. The dosages of nZVI was used as 0.2%, 1%, 5% and 10% (dry density) corresponding to the molar content of nZVI is 15, 75, 370 and 740.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the soil complexity, it is essential to set the concentration of the treatment reagents matching the contaminants. It is reported that the nZVI performed a higher removal efficiency when the molar ratio of nZVI/lead and nZVI/nitrate is 10 and 4 respectively in the solution (Su et al 2014, Moazeni et al 2017. The dosages of nZVI was used as 0.2%, 1%, 5% and 10% (dry density) corresponding to the molar content of nZVI is 15, 75, 370 and 740.…”
Section: Methodsmentioning
confidence: 99%
“…It can react with organic contaminants and heavy metal ions, including Pb 2+ , Ni 2+ , As 2+ , Co 2+ , Cu 2+ , CrO4 2-, AsO4 3-, polycyclic aromatic hydrocarbons (PAH) etc. in bench-scale and pilot-scale experiments (Mueller et al 2012, Singh et al 2012, Chekli et al 2016, Tiberg et al 2016, Wang et al 2016, Gil-Díaz et al 2017, Li et al 2017, Moazeni et al 2017. The nZVI efficiency of aqueous, contaminated groundwater was proved in many literatures.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation